Inflammatory biomarkers, vascular procedures of lower limbs, and wound healing. Issue 3 (17th February 2019) - Sapienza, Paolo; Mingoli, Andrea; Borrelli, Valeria; Brachini, Gioia; Biacchi, Daniele; Sterpetti, Antonio V.; Grande, Raffaele; Serra, Raffaele; Tartaglia, Elvira
Abstract : Abnormal, persistent inflammation after bypass surgery could prevent healing of an ischaemic foot lesion. In 37 patients with peripheral arterial disease (PAD) (Rutherford Grade III Category 5) who underwent infrapopliteal vein graft and midfoot amputation, plasma levels of fibrinogen, C‐reactive protein (CRP), interleukin‐1 (IL‐1), interleukin‐6 (IL‐6), tumour necrosis factor‐α (TNF‐α), and matrix metalloproteinase‐2 and ‐9 (MMP‐2 and MMP‐9) were determined preoperatively and during the follow up. Nine patients without clinical and Doppler evidence of arterial disease, who underwent post‐traumatic midfoot primary amputation, were included in the experiment group, and 15 age‐matched healthy volunteers served as control. In patients who had midfoot amputation for trauma, all wounds healed. Seven (19%) wounds in patients with an occluded graft healed, and five (13%) required major amputation because of a non‐healing wound. Time required for complete healing of the lesion was similar between trauma and PAD patients (8 ± 2 months vs 11 ± 6, respectively, P = NS). Univariate analysis demonstrated that, in PAD patients, the postoperative high levels of TNF‐α, IL‐6, and MMP‐2 and ‐9 were predictive for wound healing failure at 3, 6, and 9 months ( P < 0.05), respectively. Furthermore, the subgroup of patients who experienced occlusion of the vein graft during follow up had a significant increase of MMP‐2, ‐9, IL‐6, and TNF‐α at 3, 6, and 9 months ( P < 0.05), respectively. Monitoring inflammatory markers allows the determination of patients at risk of healing failure of midfoot amputation after distal revascularisation and might predict the fate of the vein graft.